Solutions of the Cahn–Hilliard equation with time-and space-fractional derivatives - Dahmani, Zoubir; Benbachir, Maamar (Int. J. Nonlinear Sci, 2009)
In this paper, by introducing the fractional derivative in the sense of Caputo, we apply the Adomian decomposition method for Cahn-Hilliard with time-and space-fractional derivative. As a result, numerical solutions are obtained in a form of rapidly convergent series with easily computable components.
Keywords: Caputo Fractional derivative; Adomian method; Cahn-Hilliard equation; Evo- lution Equations.